Influence of the follicular wave on gene expression and in vitro embryo production in cattle - Silva, N. C.; Yokomizo, D. N.; Zangirolamo, A. F.; Cavalieri, F. L.B.; Costa, C. B.; Rossignolo, E. A.A.; Dellaqua, T. T. [UNESP]; Morotti, F.; Seneda, M. M. (My University, 2025)
This study evaluated oocyte competence, gene expression, and in vitro embryo production (IVEP) in cattle, based on follicular waves. Twenty Bos taurus taurus donors were subjected to ovulation synchronization, starting with intramuscular administration of 2 mg estradiol benzoate and a 1.9 g intravaginal progesterone device on a random estrous cycle day (ten days before synchronized ovulation; D-10). After 3 days, the device was removed, and 150 μg of D-cloprostenol sodium, 300 IU of equine chorionic gonadotrophin, and 1.0 mg of estradiol cypionate were administered. Day zero (D0) was defined as the day of ovulation, and the ovaries of the females in the crossover design were examined using Doppler ultrasonography. Ovum pick-up was scheduled on days D4, D8, D14, and D18, and the experimental groups were designated as G4 (n = 5), G8 (n = 5), G14 (n = 5), and G18 (n = 5), respectively. The corpus luteum (CL) increased in diameter, perimeter, and area throughout the estrous cycle, with significant differences between G4 and other groups (P < 0.0001). CL vascularization scores on G4, G8, G14, and G18 revealed a gradual increase in peripheral blood flow(1.28, 1.79, 1.67, and 1.86, respectively). The central blood flow was higher in G8 (1.53) and G14 (1.57) than that in G4. Oocytes from each group were analyzed using reverse transcription and quantitative polymerase chain reaction after cumulus cell removal. The effect of group (OPU timing) on follicular growth waves was analyzed using ANOVA, followed by Tukey's post hoc test. All statistical analyses were conducted using Minitab statistical software version 18.1, with the significance level set at P ≤ 0.05. For evaluation of qPCR data, the 2−ΔCq method was used. Analyses were conducted using SigmaStat 4.0 and MetaboAnalyst 5.0. Differences were considered significant at P < 0.05 and/or FC > 2.0 (upregulated) or FC < 0.5 (downregulated).Total and viable oocyte numbers were lowest in G8 (13.9 and 9, respectively). The average numbers of embryos per donor were 2.58, 2.38, 2.29, and 1.69 G14, G18, G4, and G8, respectively. Gene expression analysis showed downregulation of genes related to apoptosis and lipid metabolism in oocytes retrieved from G14 compared to those from G4, G8, or G18. Oocytes from G18 showed upregulation of genes related to apoptosis control and lipid metabolism, whereas those from G4 and G8 were downregulated. In conclusion, ovum pick-up at the beginning of the second follicular wave can improve IVP efficiency.
Keywords: Biotechniques of reproduction; Doppler evaluation; Oocyte donors; RTqPCR